Dukungan Keluarga dengan Kelancaran Asi Pada Ibu Menyusui di Wilayah Kerja Puskesma Kuta Baro Aceh Besar - Khaira Rizki; Nurul Amna; Nurliza Nurliza (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2023)
Mother's milk (ASI) is rich in nutrients and is the key to baby's health. Breast milk is the best food that babies aged 0-6 months need for optimal growth and development, increasing body resistance, protecting against infection, forming a healthy digestive system and increasing intelligence. The aim of this research is to determine the relationship between family support and smooth breastfeeding for breastfeeding mothers in the Kuta Baro Aceh Besar Community Health Center working area. This research is quantitative with an analytical design using a cross-sectional study method. The population in this study were all breastfeeding mothers who had babies aged 0-6 months, totaling 139 people, using a sampling technique, namely proportional random sampling, of 58 people. Data analysis used chi square with the research results showing that there was a relationship between family support and smooth breastfeeding with a value of p = 0.011. It is hoped that respondents can use this as input to increase knowledge, understanding and information regarding family support which influences the smooth flow of breastfeeding.